A tool path generation method for quasi-intermittent vibration assisted swing cutting. (December 2020) - Zhu, Zhimin; Lu, Mingming; Lin, Jieqiong; Zhou, Jiakang; Yi, Allen; Zhuang, Xulong
During the machining of freeform surfaces, the tool path will directly affect the machining accuracy of the surface, the execution of each axis of the machine tool, and the machining efficiency. Therefore, tool path planning is a very critical link in all types of diamond turning processes. In this paper, a new tool path generation strategy is proposed for machining freeform surfaces by quasi-intermittent vibration assisted swing cutting (QVASC) method. Due to the unique tool swing motion law of QVASC, the effective central angle of tool nose arc participating in the cutting is a parameter that is ignored by traditional cutting and is considered. This makes the generation of tool trajectories, tool geometry selection and freeform surfaces very different from traditional diamond cutting. According to the principle of QVASC, the tool parameters are analysed, and the tool position is designed in the cylindrical coordinate system. Interpolation was then performed by the Hermite spline interpolation theorem. The application of this strategy is discussed, and the sinusoidal surface, sinusoidal mesh surface and toric surface are taken as examples to simulate. The simulation succeeded in obtaining the tool path corresponding to the three curved surfaces processed by the QVASC method. The results prove that the tool trajectory generation strategy proposed in this paper is feasible. The proposed tool path generation strategy can provide a new reference for future freeform surfaces processing.